Optic ataxia and the dorsal visual steam re-visited: impairment in bimanual haptic matching performed without vision - Jackson, Stephen R.; Condon, Laura; Newport, Roger; Pears, Sally; Husain, Masud; Bajaj, Nin; O'Donoghue, Michael O. (Elsevier, 2017)
The ‘two visual systems’ account proposed by Milner and Goodale (1992) argued that visual perception and the visual control of action depend upon functionally distinct and anatomically separable brain systems: a ventral stream of visual processing that mediates visual perception (object identification and recognition) and a dorsal stream of visual processing mediating visually guided action. Compelling evidence for this proposal was provided by the neuropsychological studies of brain injured patients, in particular the contrasting pattern of impaired and preserved visual processing abilities of the visual object agnostic patient (DF) and optic ataxic patients who it was argued presented with impaired dorsal stream function. Optic ataxia has thus become a cornerstone of this ‘two visual system’ account (Pisella, Sergio, Blangero, Torchin, Vighetto, Rossetti, 2009). In the current study we re-examine this assumption by investigating how several individuals presenting with optic ataxia performed on a bimanual haptic matching task performed without vision, when the bar to be matched was presented haptically or visually. We demonstrate that, unlike neurologically healthy controls who perform the task with high levels of accuracy, all of the optic ataxic patients were unable to perform the task. We interpret this finding as further evidence that the key difficulty experienced by optic ataxic patients across a range of behavioural tasks may be an inability to simultaneously and directly compare two spatial representations so as to compute the difference between them.